Archeology of the Volcanic Caves in Krong No: Historical - Cultural Significance - Le, Xuan Hung (Russia, 2023)
This article introduces the results of excavation and research on the cultural remains of prehistoric people in the volcanic caves at Krong No, Dak Nong (Vietnam). The sediments in the caves have preserved a standard stratigraphy of the prehistoric culture of the ancient people who lived there, allowing an assessment of the tools, burial characteristics, and vestiges of animals and plants. The absolute dating system (14C) has revealed continuous human habitation in the caves from 7,000 to 4,000 BP. In addition, the archeological evidence from the volcanic caves at Krong No provides important information about the past environment, evolutionary history and diversity of nature, adaptation of people to changes in the environment, and their spiritual culture (from burial documents). Clear findings on the characteristics of the ancient fauna and flora are not commonly found in the archeological evidence of the Central Highlands volcanic region of Vietnam and Southeast Asia.